2020
DOI: 10.3390/pathogens9090671
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Rotavirus A Strains Pre- and Post-Vaccine (Rotarix®) Introduction in Mozambique, 2012–2019: Emergence of Genotypes G3P[4] and G3P[8]

Abstract: Group A rotavirus (RVA) remains the most important etiological agent associated with severe acute diarrhea in children. Rotarix® monovalent vaccine was introduced into Mozambique’s Expanded Program on Immunization in September 2015. In the present study, we report the diversity and prevalence of rotavirus genotypes, pre- (2012–2015) and post-vaccine (2016–2019) introduction in Mozambique, among diarrheic children less than five years of age. Genotyping data were analyzed for five sentinel sites for the periods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 49 publications
(93 reference statements)
3
25
0
Order By: Relevance
“…Page and colleagues found a significant decrease in G1 strains post vaccine introduction in SA (2009–2014), with a corresponding increase in non G1P[8] strains [ 70 ]. A recent study from Mozambique reported the emergence of G3P[4] and G3P[8] in the post vaccine era, with G3P[4] increasing from 2.6% prevalence in 2016 to 38.7% in 2018 [ 71 ], correlating with the predominance of G3P[4] observed in 2016/2017 at KPTH. More recent studies have now included whole-genome sequencing of rotaviruses [ 72 , 73 ], to give a better overall perspective on the specific strains detected, their origin and reassortment, this should be considered for future studies, to improve our understanding of rotavirus epidemiology.…”
Section: Discussionmentioning
confidence: 99%
“…Page and colleagues found a significant decrease in G1 strains post vaccine introduction in SA (2009–2014), with a corresponding increase in non G1P[8] strains [ 70 ]. A recent study from Mozambique reported the emergence of G3P[4] and G3P[8] in the post vaccine era, with G3P[4] increasing from 2.6% prevalence in 2016 to 38.7% in 2018 [ 71 ], correlating with the predominance of G3P[4] observed in 2016/2017 at KPTH. More recent studies have now included whole-genome sequencing of rotaviruses [ 72 , 73 ], to give a better overall perspective on the specific strains detected, their origin and reassortment, this should be considered for future studies, to improve our understanding of rotavirus epidemiology.…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, the World Health Organization (WHO) proposed the implementation of rotavirus vaccines in routine vaccination systems worldwide and, in particular, in countries with a high incidence of diarrhoea-related mortality below 5 years of age [ 6 ]. The post-vaccination monitoring studies showed a substantial reduction in RVA prevalence in the countries where the Rotarix™ vaccine was widely used [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The detection of the unusual G9P[4] strain (RVA/Human-wt/RWA/UFS-NGS:MRC-DPRU566/2013/G9P[4]) in Rwanda is noteworthy as it is more prevalent in South-East Asia, Japan and Central America and detected at very low frequency (2%) in Africa [ 23 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Phylogenetic analysis revealed that the five Rwandan strains clustered mostly with strains circulating globally, with few exceptions that clustered separately.…”
Section: Discussionmentioning
confidence: 99%